Rancang Bangun Sistem Informasi Analisis Kebutuhan Diklat Bagi Guru SMK di Dispendik Provinsi Jawa Timur - Sugiarto, Kristono; Sunarto, M.J. Dewiyani; Maulana, Yoppy Mirza (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2016)
Abstract: Unit Pelaksana Teknis (UPT) Pelatihan dan Pengembangan Pendidikan Kejuruan (PPPK) is a technical and operational unit of Dinas Pendidikan (Dispendik) East Java Regional that take care of training and vocational education development. UPT PPPK has a main task to organize training and vocational education development, administration, and public services. UPT PPPK has a Educational Services Division (Seksi Pelayanan Pendidikan) which suppose to organize training for Vocational High School’s teachers in Each Java Regional.Whilst there are almost 1500 Vocational High Schools, arround 36.000 teachers, and 211 vocationals in East Java which is impossible to organize all vocationals in a year. To overcome these conditions UPT PPPK needs a solution system that could assist to determining which teacher that need training the most. Collecting and analyzing data in order to identify what subjects or elements inside the organization that need to be enhanced for the sake of increasing organization’s productivity is what called as Training Need Analysis.Based on result of testing and evaluation, the application success to determining the gap that need training for the teacher through exam as placement test and teacher's training history. Whilst this gap would lead UPT PPPK to give a proper training and determining the training's participants.